REDESCRIPTION OF SOME INDIAN LEPIDOCYRTUS SP. (COLLEMBOLA-ENTOMOBRYIDAE) - M. RAGHURAMAN; SANTESHWARI; J. SINGH (The Bioscan, 2014)
The genus Lepidocyrtus of collembola (Arthropleona - Entomobryidae) has been described. The species Lepidocyrtus lignorum and L. curvicollis are reported for the first time from India. The specimens were collected from soil litter. L. curvicollis and L. lignorum has characterized by the presence of scales on the Ist and IInd segments of antennae, legs beyond coxae and dorsal side of manubrium. The species L. lignorum is characterized by normal mesonotum. Presence of R marcochaetae on head but S and T setae absent. On abd. 4 lateral macrochaeta E1 set between L2 and L3. L. curvicollis is characterized by mesonotum hood-like projecting, blunt at tip. Head without macrosetae. R S and T microsetae present. On abd. 4 lateral macrochaeta E1 set behind L2. Unguiculus of L. curvicollis shows serrated structure.